Neuroprotective Activity of Thioctic Acid in Central Nervous System Lesions Consequent to Peripheral Nerve Injury. (29th December 2013) - Tomassoni, Daniele; Amenta, Francesco; Di Cesare Mannelli, Lorenzo; Ghelardini, Carla; Nwankwo, Innocent E.; Pacini, Alessandra; Tayebati, Seyed Khosrow
Abstract : Peripheral neuropathies are heterogeneous disorders presenting often with hyperalgesia and allodynia. This study has assessed if chronic constriction injury (CCI) of sciatic nerve is accompanied by increased oxidative stress and central nervous system (CNS) changes and if these changes are sensitive to treatment with thioctic acid. Thioctic acid is a naturally occurring antioxidant existing in two optical isomers (+)- and (−)-thioctic acid and in the racemic form. It has been proposed for treating disorders associated with increased oxidative stress. Sciatic nerve CCI was made in spontaneously hypertensive rats (SHRs) and in normotensive reference cohorts. Rats were untreated or treated intraperitoneally for 14 days with (+/−)-, (+)-, or (−)-thioctic acid. Oxidative stress, astrogliosis, myelin sheets status, and neuronal injury in motor and sensory cerebrocortical areas were assessed. Increase of oxidative stress markers, astrogliosis, and neuronal damage accompanied by a decreased expression of neurofilament were observed in SHR. This phenomenon was more pronounced after CCI. Thioctic acid countered astrogliosis and neuronal damage, (+)-thioctic acid being more active than (+/−)- or (−)-enantiomers. These findings suggest a neuroprotective activity of thioctic acid on CNS lesions consequent to CCI and that the compound may represent a therapeutic option for entrapment neuropathies.